Shear ruptures of extreme dynamics in laboratory and natural conditions - Tarasov, BG (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
In the Earth’s crust shear ruptures are responsible for macroscopic dynamic failure causing earthquakes. Shear ruptures induced by and triggered by the mining-induced stress change sometimes result in damaging rockbursts. The fundamental mechanism of the shear rupture is critically linked to the magnitude of ground motion, and hence, any resulting damage. For the effective management of seismic hazard both from natural and mining-related causes, a comprehensive understanding of the fundamental mechanism of the shear rupture is crucial. In recent years it has been observed that shear ruptures can propagate with extreme velocities exceeding the shear wave speed. Experiments show that a remarkable feature of extreme ruptures is the fact that friction reduces toward zero in the rupture head. Coseismic reduction in friction is critical in accelerating the fault slip and to the magnitude of ground shaking which affects the amount of potential earthquake and rockburst damage. Despite the critical importance, physical processes which determine the dramatic weakening of friction are still unclear and continue to be vigorously debated. The second unresolved question is about the source of energy which provides extreme rupture dynamics. This paper shows that the nature of extreme ruptures in intact rocks and in pre-existing faults with frictional and coherent interfaces is the same. It demonstrates that in all types of extreme ruptures, the fault weakening can be explained by a recently-proposed shear rupture mechanism associated with the intensive tensilecracking process in the rupture tip observed for all extreme ruptures. The tensile-cracking process creates, in certain conditions, a fan-like fault structure, the shear resistance of which is extremely low. The fan-structure represents the basis of a self-sustaining natural mechanism of stress intensification in the rupture head providing the driving power for rupture propagation with extreme velocities. The fanmechanism causes dramatic embrittlement of intact hard rocks under high stress and makes transient strength of intact hard rocks during the rupture propagation significantly less than the frictional strength. This paper introduces features of the fanmechanism operation in primary ruptures and in natural complex faults and proposes an alternative view on the nature of earthquakes and shear rupture rockbursts generated by extreme ruptures.
Keywords: super shear